Noradrenergic Signaling in Infralimbic Cortex Increases Cell Excitability and Strengthens Memory for Fear Extinction - Mueller, Devin (J Neurosci, 2008)
Emotional arousal strengthens memory. This is most apparent in aversive conditioning, in which the stress-related neurotransmitter norepinephrine (NE) enhances associations between sensory stimuli and fear-inducing events. In contrast to conditioning, extinction decreases fear responses, and is thought to form a new memory. It is not known, however, whether NE is necessary for extinction learning. Previous work has shown that the infralimbic prefrontal cortex (IL) is a site of extinction consolidation. Here, we show that blocking noradrenergic β-receptors in IL before extinction training impaired retrieval of extinction the following day, consistent with a weakened extinction memory. We further found that the sequelae of β-receptor activation, including protein kinase A (PKA), gene transcription and translation in IL, are necessary for extinction. To determine whether activation of this cascade modulates IL excitability, we measured the response of IL pyramidal neurons to injected current. NE increased the excitability of IL neurons in a β-receptor- and PKA-dependent manner. We suggest that NE released in IL during fear extinction activates a PKA-mediated molecular cascade that strengthens extinction memory. Thus, emotional arousal evoked by conditioned fear paradoxically promotes the subsequent extinction of that fear, thereby ensuring behavioral flexibility.